Principles of Toxicology Applied to Nanotechnology - Silva, Maria João (2020)
Summary: Principles of Toxicology/genotoxicology. Nanotoxicology. Safety evaluation of cellulose nanofibrils (CNF): genotoxic effects in human cell lines.